The transcriptions of the Three Teachers: an old or a new sound? - Arvanitis, Ioannis (Epistēmēs Metron Logos, 2022)
200 years ago, the Ecumenical Patriarchate called a synod, to honour the Three Teachers, that is the three reformers of the notational system of Eastern Orthodoxy’s ecclesiastical chant tradition: Chrysanthos of Madytos, Archimandrite and subsequently Archbishop of Dyrrachium (modern day Durrës, Albania), Gregorios the Lampadarios and then Protopsaltis of the Great Church, and Chourmouzios, a music teacher, then honoured with the officium of Archivist. The synod gave an official status to their so-called New Method (hereafter abbreviated as NM) and issued an encyclical inviting all cantors to Constantinople to learn this method. 200 years later, the music-loving mood of this journal’s publishers brought us as well, to honour these men. Although mentalities and psaltic habits might have changed, we understand ourselves descendants from these three men whom we see as benefactors, and therefore we also feel the duty to honour them.